Do governance mechanisms promote informative earnings management? Evidence from a two-tier board system - Adhitya Agri Putra (JIFA (Journal of Islamic Finance and Accounting), 2025)
This study examines whether corporate governance mechanisms promote informative earnings management within a two-tier board system, addressing the ongoing debate on whether earnings management is beneficial or opportunistic. While prior studies largely focus on developed markets and treat earnings management as detrimental, limited evidence explores its informative role in emerging economies. Using a sample of 516 firm-year observations of manufacturing firms listed on the Indonesia Stock Exchange during 2016–2021, this study employs logistic regression analysis to test the effect of ownership concentration, board independence, and audit committee expertise on informative earnings management. The findings show that ownership concentration and board independence significantly enhance the likelihood of informative earnings management, suggesting that effective monitoring mechanisms reduce information asymmetry and encourage managers to communicate firm prospects more transparently. However, audit committee expertise does not show a significant effect, indicating potential limitations in its monitoring effectiveness. This study concludes that certain governance mechanisms can support more informative financial reporting rather than merely constraining managerial behavior. The results contribute to the literature by distinguishing between different motivations behind earnings management and provide practical implications for regulators and investors in strengthening governance structures to improve the informativeness of reported earnings.